HUMAN-MACHINE COMMUNICATION: ETHICAL PERSPECTIVES - Jones, Steve; Guzman, Andrea; Conner, Thomas; Pashevich, Ekaterina (AoIR Selected Papers of Internet Research, 2020)
Digital voice assistants, social robots, artificial intelligence and progressively refined algorithms are ushering in new modes of interaction that increasingly mediates between human and machine. This panel will engage ethical questions related to those modes of interaction, ranging from discussion of automated journalism to virtual performers, digital research assistants to toys. The central concern among the papers to be presented is to probe the nature of the relationships forged between humans and machines when the latter are interlocutors and creators and not merely passive recipients of data through interaction. What new ethical issues are emerging as machines create journalism, as they create music and interact in performance, as they engage in research, as they become a part of childrens’ social circle?